Finding Genius Loci of Kauman Yogyakarta - Saputra, Indra Tri; Agustiananda, Putu Ayu P.; Sinaga, Bryan Putra Parsada (Journal of Architectural Design and Urbanism, 2024)
Kauman Yogyakarta is a village located in the Ngupasan sub-district in Gondomanan sub-district, Yogyakarta to the north of the Nyayogyakarta Palace. The location close to the Yogyakarta Palace, Kauman Yogyakarta has an interesting uniqueness to explore using the Genius Loci theory. To find the Genius Loci in Kauman Yogyakarta, an approach was taken using an architectural phenomenology approach. The results of this research add to references in the literature by using an architectural phenomenology approach based on the Genius Loci theory and maintaining Genius Loci in Kauman Yogyakarta.